2017
DOI: 10.1017/ice.2017.189
|View full text |Cite
|
Sign up to set email alerts
|

Failure to Communicate: Transmission of Extensively Drug-ResistantblaOXA-237-ContainingAcinetobacter baumannii—Multiple Facilities in Oregon, 2012–2014

Abstract: OBJECTIVE To determine the scope, source, and mode of transmission of a multifacility outbreak of extensively drug-resistant (XDR) Acinetobacter baumannii. DESIGN Outbreak investigation. SETTING AND PARTICIPANTS Residents and patients in skilled nursing facilities, long-term acute-care hospital, and acute-care hospitals. METHODS A case was defined as the incident isolate from clinical or surveillance cultures of XDR Acinetobacter baumannii resistant to imipenem or meropenem and nonsusceptible to all but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The surveillance source was axillary/groin. The A. baumannii isolates were initially selected due to their high-level carbapenem resistance and were a subset of 21 cases identified during this study (13). These 16 isolates were physically available for further molecular characterization.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The surveillance source was axillary/groin. The A. baumannii isolates were initially selected due to their high-level carbapenem resistance and were a subset of 21 cases identified during this study (13). These 16 isolates were physically available for further molecular characterization.…”
Section: Resultsmentioning
confidence: 99%
“…Setting and selection of isolates. Sixteen A. baumannii isolates carrying bla OXA-237 reported in this study were initially selected due to their high-level carbapenem resistance and were a subset of 21 cases identified during this study (13). The bla OXA-237 -positive A. baumannii AF684 strain was included as a control for comparison purposes (9).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last 10 years, Acinetobacter baumannii has emerged as one of the major pathogens implicated in outbreaks of hospital-acquired infections, especially in patients from intensive care units (ICUs; Maragakis and Perl, 2008 ; Eveillard et al, 2010 ; Buser et al, 2017 ). Historically, carbapenems are the most potent and reliable β-lactam antibiotics for the treatment of serious infections caused by A. baumannii ( Garnacho-Montero and Amaya-Villar, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, this study represents the third reported identification of the acquired class D carbapenemase bla OXA-237 , and its first identification in Canada. The bla OXA-235-like subclass, which includes bla OXA-237 , was first recognised from A. baumannii isolates in the United States and Mexico in 2013 [ 34 ] and was implicated in a multi-center outbreak in Oregon between 2012 and 2014 [ 35 ]. This resistance gene was located on a plasmid found in the most prominent A. baumannii clonal group, representing a potential for extensive dissemination [ 36 ].…”
Section: Discussionmentioning
confidence: 99%